The effects of Interleukin-6 on viability, redox homeostasis and migration capacity of human placental cells JEG-3 in chemically induced hypoxia - Matić, Miloš; Obradović, Ana; Milošević, Marija; Paunović, Milica; Ognjanović, Branka (Kragujevac Journal of Science, 2022)
Interleukin-6 (IL-6) is a pleiotropic cytokine involved in the regulation of cell growth and differentiation exerting an important role in the immune and inflammatory response. This study aimed to evaluate the effects of three increasing concentrations of IL-6 (1 pg/mL, 5 pg/mL, and 10 pg/mL) on cell viability, redox homeostasis parameters (O2∙, NO2-, glutathione) and migratory potential in human trophoblast cell line JEG-3 under chemically induced hypoxia in short-term (24 h) and long-term (72 h) exposure. The obtained results show a dose-dependent reduction of cell viability and NO levels, while the concentration of O2 ∙increased. Levels of total glutathione increased in a dose-dependent manner compared to control cells, suggesting its significant antioxidative contribution in hypoxic conditions. The migratory potential of cells was significantly elevated in the two highest applied doses implying the disturbance of cell invasive homeostasis at its pathological concentrations, which could represent a risk factor in some pregnancy disorders.